ASSOCIATION OF THE RS1799750 MATRIX METALLOPROTEINASE-1 GENE POLYMORPHISM AND CORONARY ARTERY DISEASE IN YOUNG MACEDONIAN POPULATION - Boshev, Marjan; Stankovic, Svetlana; Panov, Sasho; Josifovska, Slavica; Pakovski, Kiril; Kedev, Sasko; Pejkov, Hristo (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Coronary artery disease (CAD) is very complex disease arising from close interaction of many risk-factors as well as presence of many comorbidities. Pathophysiology mechanisms may be different and encompass endothelial dysfunction, impaired lipid metabolism, chronic inflammation, thrombosis, and mechanisms associated with tissue maintenance and remodeling. In this research we aim to investigate the association between rs1799750 (-1607 1G/2G) matrix metalloproteinase – 1 (MMP-1) gene polymorphism and CAD in young Macedonian population. This is an observational, genetic-association study of cases and controls including 57 participants divided into two groups. The first is the group with positive coronary angiography (CA) finding (n=34) and the second is the group with negative CA finding (controls, n=34 participants). All of them underwent molecular and genetic analyses after performed CA. Complete comparison of the frequencies of genotypes and alleles of the rs1799750 MMP-1 gene polymorphism was used for statistical analysis. Calculations were performed using Chi-square test (x 2 -test) and Fisher's exact test for analysis of the genotype and allele frequencies of the gene polymorphism using five different models. The Cochran-Armitage trend test was used to analyse the allelic frequencies with the allelic and additive model. The statistical analyses were performed using XLSTAT 2016, GenAIEx 6.5 and Microsoft Excel 2016 software. According to the genotypic model, carriers of the heterozygous 1G/2G genotype have 2,8 times higher probability whereas carriers of the 2G/2G genotype have 7,389 times higher probability for development of CAD in comparison to the reference carriers of 1G/1G, respectively (p<0,05). The dominant model has also confirmed that genotype carriers with at least one 2G allele have 4,521 times higher probability for CAD in comparison to homozygous 1G/1G genotype carriers (p<0,05). According to the recessive model, participants with homozygous 2G/2G genotype have statistically significant 3,589 times higher probability for CAD in comparison to participants with at least one 1G allele (p<0,05). Allelic model also proved that carriers of the 2G allele have 3 times higher chances for development of CAD than the carriers of the 1G allele (p<0,05). The last, additive model, confirmed that the risk increases with the number of present 2G allele. Results from our study clearly show that there is statistically significant genetic association of the rs1799750 MMP-1 gene polymorphism with significant CAD in young Macedonian population. More specifically, presence of genotype 2G/2G as well as allele 2G leads to statistically significant increase of the probability for CAD. Key words : CAD, MMP-1, gene polymorphism, rs1799750.